Book review: Pentecost, This story is our story - by Robert P. Menzies - Victor Christianto (Sekolah Tinggi Teologi Satyabhakti, Malang, 2023)
Ulasan buku kali ini adalah mengenai karya Dr. Robert P. Menzies, Pentecost: This story is out story.